Elephants under human care : the behaviour, ecology, and welfare of elephants in captivity - Rees, Paul A. (Academic Press, an imprint of Elsevier, 2021)
This book draws together, for the first time, the published research on the behaviour, ecology and welfare of elephants living in zoos, circuses, logging camps and other captive environments in a single comprehensive volume. It takes a multi-disciplinary approach, considering the work of zoo biologists, animal behaviour and welfare scientists, veterinarians, philosophers, zoo educators, tourism specialists, conservation biologists, lawyers and others with a professional interest in elephants. Elephants under Human Care: The Behaviour, Ecology, and Welfare of Elephants in Captivity is a valuable resource for zoo biology and animal welfare researchers. It is also useful for students and zoo professionals and managers looking for a comprehensive guide to current research on captive elephants. Although not intended as a husbandry manual, the book discusses some of the elephant welfare standards developed by the Association of Zoos and Aquariums (AZA) and the British and Irish Association of Zoos and Aquariums (BIAZA) and their relationship to current knowledge of captive elephants. --